Manajemen Pendidikan dalam Era Globalisasi - Made Pidarta (Universitas Negeri Malang, 2016)
Human resources in the global era should be creative, competitive, and science and technological oriented. This quality will be achieved if education is aimed at creating opportunities to develop the students' affection to learn from or by themselves. Educational process should apply a heuristic approach characterized by utilization of enquiry methods, experiments, projects, etc. The existing educational institutions should be handled by a perfect educational management. It is a management emphasizing the needs of educational consumers, aspecially students, optimizing role of the senate or school council as motor and source of ideas for development of the institution, utilizing a decentralization system, mobilizing public funds to speed up the institution, applying the principle of peosonnels' participation, and improving community cooperation and control